Tactical network planning and design in multimodal transportation – A systematic literature review. (June 2020) - Elbert, Ralf; Müller, Jan Philipp; Rentschler, Johannes
Abstract: Multimodal transportation, which refers to the combination of different modes in a transportation chain, can be a cost-efficient and green alternative to unimodal road transportation in the carriage of goods. However, the complex transportation processes require network flow planning and design models on a tactical level covering the multiple stages and paths of a multimodal network for determining cost-minimal and reliable operations. This paper summarizes the current state of research since 2008 on the specific categories of those models by the means of a systematic literature review. The references within each category are evaluated in terms of problem characteristics, model formulations and solution approaches. Moreover, the research streams on deterministic and stochastic models (including uncertain demand, transportation times, costs and capacities) are compared. Finally, main fields for future research, among others the further inclusion of environmental aspects and the more frequent application of simulation as solution approach, are identified.